Relationship Patterns of Fishermen With Employer in Kepenghuluan Teluk Pulau Hulu, Rimba Melintang District, Rokan Hilir, Riau - Syarifah Aini; Eni Yulinda; Kusai ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted on 17th until 24th June 2013 in the GulfKepenghuluan Hulu Island Wilderness Crossing District of Rokan Hilir RiauProvince. The purpose of this study was to: Describe and analyze the relationshipbetween the fishermen form the employer and Analyze advantages anddisadvantages of fishermen and a relationship with the employer when theemployer in the Upper Subdistrict Kepenghuluan Jungle Island Bay Crossing.Further analyzed in the form of descriptions using descriptive analysis reveals aproblem, situation or event as it is.Pattern of relationships with the employer fishermen in the GulfKepenghuluan Hulu Island interwoven harmoniously without harming next party,because the two are mutually beneficial. Pattern of the relationship is not only thepattern of labor relations, but also the pattern of social relations, patterns ofemotional relationships and patterns of cultural relations. A relationship can notbe separated from the profits and losses incurred by fishermen and employer.Fishermen advantages was financial insurance by loan from employer. Employeradvantages was fish stock by fishermen catch. Disadvantages of this relationshipwas fishermen’s interdepedence to employer. Because of close relationship bothof them, fishermen was not be able to affect sale price of that fish. On the otherhand, employer got worst quality of fishermen’s catch when the catch wasabundant and loss of cost when was little catch.Keyword : Fisherment, Employer, Teluk Pulau Hulu, Patron Client Fisheries